POLYMERASE CHAIN REACTION AND SEROLOGY TEST TO DETECT RUBELLA VIRUS IN CONGENITAL RUBELLA SYNDROME PATIENTS WITH HEARING LOSS - Izzattisselim, Sabrina; Purnami, Nyilo (Institute of Topical Disease Universitas Airlangga, 2020)
Rubella infections in pregnant women, especially during the first trimester, often lead to manifest as congenital rubella syndrome (CRS). This syndrome consists of several inherited disorders such as deafness, cataracts, and cardiac abnormalities. Deafness is the most common manifestation of CRS, 70-90% of all cases with deafness type are sensory neural deafness. The mechanism of hearing loss due to rubella virus is caused by hypoxia resulting from endothelial vascular damage in cochlea, followed by cell death in the organ of Corti and stria vascularis.Cochlea's stria damage makes alterations in the composition of endolymph. This study aimed to confirm rubella infection using PCR and serological tests in patients with CRS who were clinically deaf. A suspected CRS reported was a 2-month-old patient with an unclear response to surround sound. The patient had been already diagnosed with congenital cataracts before. Prenatal, perinatal and postnatal history was evaluated. Hearing screening was done by OAE (Biological), and AABR (Beraphone). Anti-rubella IgM and IgG was obtained from blood serum. PCR was carried out from a throat swab and the eye-lens specimen. OAE and AABR results ‘refer' to both sides of the ear indicated a sensorineural hearing loss. The serological examination of IgM was positive with an index of 15.00 and IgG rubella positive with a titer> 500 IU / ml. Positive results from the rubella virus were identified from the throat swab and lens specimens using the PCR method. Detection of rubella virus in CRS sufferers with clinical deafness of both ears gives positive results using PCR and serology methods. In the future PCR can be potential for prenatal diagnosis of rubella virus aimed at the provision of early prevention.